2011
DOI: 10.1038/jid.2010.326
|View full text |Cite
|
Sign up to set email alerts
|

Axl Promotes Cutaneous Squamous Cell Carcinoma Survival through Negative Regulation of Pro-Apoptotic Bcl-2 Family Members

Abstract: Expression of Axl, a receptor tyrosine kinase, is increased in cutaneous squamous cell carcinoma (SCC). Examination of a series of cutaneous SCC tumors revealed positive phospho-Akt (P-Akt) staining accompanied by weak TUNEL staining in Axl-positive tumors, suggesting an anti-apoptotic role for Axl in SCC survival. The role of Axl in UV-induced apoptosis was investigated in a cutaneous SCC cell line using retroviral short hairpin RNA sequences enabling stable Axl knock-down. We show that, although Axl knock-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…3). Activation of Axl induces proliferation [149,150], survival [151][152][153][154], resistance against apoptosis [151,155,156], migration and invasiveness of cancer cells [149][150][151][152][153][154]. Furthermore, Axl mediates resistance towards chemo-and targeted therapy including anti-VEGF or anti-EGFR therapy in part by inducing secretion of proinflammatory and protumoral cytokines such as IL-6, TNFa and G-CSF in TAMs, where it is highly expressed [157].…”
Section: Macrophages and Cancer Therapy Resistancementioning
confidence: 99%
“…3). Activation of Axl induces proliferation [149,150], survival [151][152][153][154], resistance against apoptosis [151,155,156], migration and invasiveness of cancer cells [149][150][151][152][153][154]. Furthermore, Axl mediates resistance towards chemo-and targeted therapy including anti-VEGF or anti-EGFR therapy in part by inducing secretion of proinflammatory and protumoral cytokines such as IL-6, TNFa and G-CSF in TAMs, where it is highly expressed [157].…”
Section: Macrophages and Cancer Therapy Resistancementioning
confidence: 99%
“…Extrinsic pathway which is triggered through death receptors and intrinsic one which is caused by mitochondrial alterations. In the extrinsic pathway, cell death depends on amounts of various members of Bcl2 family [22]. On the other hand, targeting the AKT/GSK3β/cyclin D1/Cdk4 pathway can be an efficient modality to suppress cell cycle to acquire radio resistance of tumor cells [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the exact inhibition of apoptosis by Axl and the anti-apoptotic mechanisms in osteosarcoma have been rarely reported [21]. ES Papadakis et al have confirmed that Axl could negatively regulate pro-apoptotic Bcl-2 family members and promote cellular survival in cutaneous squamous cell carcinoma [22]. It is interesting to determine whether there is a similar mechanism for Axl to control apoptosis in osteosarcoma.…”
mentioning
confidence: 99%
“…39 The same applies to Nilotinib. 40 Axl overexpression and/or activation has been related to resistance to chemotherapy in some other cancer types ; gastrointestinal stromal tumor cell lines 41 , rhabdomyosarcoma 42 , HER-2 positive breast tumor cells 43 , cutaneous squamous cell carcinoma (SCC) 44 , Kaposi sarcoma 45 and ovarian cancer. 46 Drugs targeting Axl are currently under investigation.…”
Section: Gas6/axl In Different Cancer Typesmentioning
confidence: 99%